Superhydrophilic graphene oxide@electrospun cellulose nanofiber hybrid membrane for high-efficiency oil/water separation. (1st November 2017) - Ao, Chenghong; Yuan, Wei; Zhao, Jiangqi; He, Xu; Zhang, Xiaofang; Li, Qingye; Xia, Tian; Zhang, Wei; Lu, Canhui
Highlights: Superhydrophilic GO@CNF membrane was fabricated for the first time. The micro/nanoscale hierarchical roughness surface was created through a facile method. The membrane exhibited high water flux and superior antifouling performance. The membrane was capable to separate oil/water mixtures in harsh environment. Abstract: Inspired from fishscales, membranes with special surface wettability have been applied widely for the treatment of oily waste water. Herein, a novel superhydrophilic graphene oxide (GO)@electrospun cellulose nanofiber (CNF) membrane was successfully fabricated. This membrane exhibited a high separation efficiency, excellent antifouling properties, as well as a high flux for the gravity-driven oil/water separation. Moreover, the GO@CNF membrane was capable to effectively separate oil/water mixtures in a broad pH range or with a high concentration of salt, suggesting that this membrane was quite promising for future real-world practice in oil spill cleanup and oily wastewater treatment.